Comparison of mortality and survival without major morbidities of very preterm infants with very low birth weight from Japan and Brazil - Tomo,Caroline Kaori (2023)
Abstract Objective: This study was carried out to understand the disparities in mortality and survival without major morbidities among very premature and very low birth weight infants between participating Neonatal Intensive Care Units (NICUs) from the Brazilian Network on Neonatal Research (RBPN) and the Neonatal Research Network of Japan (NRNJ). Methods: Secondary data analysis of surveys by the RBPN and NRNJ was performed. The surveys were conducted in 2014 and 2015 and included 187 NICUs. Primary outcome was mortality or survival without any major morbidity. Logistic regression analysis adjustment for confounding factors was used. Results: The study population consisted of 6,406 infants from the NRNJ and 2,319 from the RBPN. Controlling for various confounders, infants from RBPN had 9.06 times higher adjusted odds of mortality (95%CI 7.30–11.29), and lower odds of survival without major morbidities (AOR 0.36; 95%CI 0.32–0.41) compared with those from the NRNJ. Factors associated with higher odds of mortality among Brazilian NICUs included: Air Leak Syndrome (AOR 4.73; 95%CI 1.26–15.27), Necrotizing Enterocolitis (AOR 3.25; 95%CI 1.38–7.26), and Late Onset Sepsis (LOS) (AOR 4.86; 95%CI 2.25–10.97). Conclusions: Very premature and very low birth weight infants from Brazil had significantly higher odds for mortality and lower odds for survival without major morbidities in comparison to those from Japan. Additionally, we identified the factors that increased the odds of in-hospital neonatal death in Brazil, most of which was related to LOS.